Справжнє походження оповідання «Хуан Осо» - Мак-Дауелл, Д. (Народна творчість та етнологія, 2012)
John McDowell. The True Lineage of «Juan Oso». A cohesive narrative, a tale-type story «John the Bear» or «Juan Oso» is analyzed in the article of John H. McDowell. The author inspects the thesis that the native American narrative corpus, and the plot of «John the Bear» as its element, both originate in European sources. After considering the presence of the same plot in two New World collections, Robert Lowie’s Assiniboine myths and his own Kamsá mythic narratives, the author proposes that «Juan Oso» is a special case in an endemic American corpus of tales featuring amorous bears.